Dry machining of T6061 aluminium alloy using titanium nitride (TiN)and titanium carbonitride (TiCN) coated tools - Mohamed Ariff, Tasnim Firdaus; Paimin, Muhamad Fahmie; Hassan, Abdirahman (Trans Tech Publications Ltd., Switzerland, 2013)
Dry machining is a clean machining process and it will be considered as a necessity for manufacturing industries in future.Dry machining is environmental friendly and safe to be performed. Regardless of decreasing tool life due to lack of lubricants, choosing dry machining over wet machining may be a wiser choice since the cost of purchasing and disposing the cutting fluids can contribute to a higher cost. Tool wear intensities of TiN and TiCN coated tools using both dry and traditional wet machining was studied with the aim in finding the optimum cutting speed from three different cutting speeds (318, 394 and 490 m/min) with a feed rate of 0.6 mm/rev and depth of cut of 0.4 mm. Tool tip temperature was also analyzed to see the effect of temperature rise at the tool-chip interface. TiCN coated tool performed better than TiN coated tool since the wear rate for TiCN coated tool is smaller by 40-48 % when compared to TiN coated tool for dry machining for all three cutting speeds. The optimum cutting speed for dry machining of T6061 Aluminium alloy using TiN and TiCN coated tools is 394 m/min. Tool tip temperature for dry machining is also slightly higher than wet machining by 19 and 32 % for TiN and TiCN coated tools respectively at the optimum cutting speed. Dry machining of T6061 Aluminium alloy can be a more suitable eco-friendly machining process particularly at high cutting speed for interrupted cutting operations.